Filtration rate of the marine clam, Kaltelysia sp. at different light intensities and fed with microalgae Isochrysis galbana and Chaetoceros calcitrans. - Bravo, Agnes Therese Aldon
Filtration rate of the marine clam, Katelysia with body lengths ranging from 5-6 cm. and body weight from 45-65 g. were determined by using the indirect method of suspension depletion and monitored by direct algal cell count. The effects of light intensity and algal species on the feeding behavior of the clam were determined. The first treatment involves total darkness where the basis with the clams were placed under ordinary light condition (12h light ; 12h dark) and in the third treatment, the basins with the clams were positioned under a 20-watt bulb with continuous illumination (24h light)